Accelerated solvent extraction-gel permeation chromatography-gas chromatography-tandem mass spectrometry to rapid detection of clotrimazole residue in animal-derived food. (June 2021) - Han, Chao; Hu, Beizhen; Jin, Na; Jin, Jianchang; Yu, Zuolong; Huang, Chaoqun; Shen, Yan
Abstract: In this study, accelerated solvent extraction (ASE) and gel permeation chromatography (GPC) were used for the extraction and cleanup of clotrimazole residue in animal-derived food (pork, chicken, beef, fish, beef kidney and chicken liver), and gas chromatography-tandem mass spectrometry (GC-MS/MS) was used for qualitative and quantitative analysis. Matrix-matched calibration combined with an isotope internal standard overcame the matrix effects and achieved correct recovery. The average recoveries were 75.4–109.3%, with RSD ≤7.2%. The limits of quantification were 1.0 μg/kg. The detected positive samples were further confirmed by gas chromatography-quadrupole-orbitrap high-resolution mass spectrometry (GC-Orbitrap HRMS), which ensured the accuracy of the results. The developed method is rapid, accurate, and sensitive and can be applied for the determination of clotrimazole residue in animal-derived food. Highlights: Determination of clotrimazole residue in animal-derived food by GC-MS/MS. The accuracy of the results is based on SRM mode and GC-HRMS. Isotope internal standard and matrix-matched calibration were used. The structure analysis of clotrimazole was carried out for the first time.